Memberdayakan Partai Politik dalam Era Multipartai - Bambang Cipto (Unisia, 1999)
The adaption of Multiparty. System has been considered to be the best way to reach Democracy. This writing has been based on standardized theoritical assumptions and on empirical experiences of some particular countries in applying the Multiparty System. At the same token, this article also provides a more comprehensive answer about the prospect as well as the threat faced by the system. This article has not merely based on the dream of developed countries applying the system for relatively long time.